The relationship between body mass index and vertebral rotation deformity in adolescents with idiopathic scoliosis - Ida Ayu Jelantik Ari Parmitha; Gede Parta Kinandana; Ni Luh Nopi Andayani; Ni Luh Putu Gita Karunia Saraswati (Physical Therapy Journal of Indonesia, 2024)
Background: Vertebral rotational deformity is a change in the structure and shape of the spine that can be seen when observed from the transverse plane. Abnormal body mass index can affect vertebral rotational deformity in adolescents with adolescent idiopathic scoliosis. This study aimed to determine the relationship between body mass index and vertebral rotation deformity in adolescents with adolescent idiopathic scoliosis.Methods: The study used an observational analytic approach with a cross-sectional approach. The study used the sampling technique of simple random sampling and obtained 90 samples. Data was collected by measuring body mass index (BMI) and vertebral rotation deformity. BMI values were obtained by measuring body weight divided by square meters of height, while the Adam forward bending test measured the vertebral rotational deformity using a scoliometer. Results: Based on the Spearman Rho non-parametric analysis test, the p-value = 0.000 (p < 0.05) and the correlation coefficient r = 0.657, meaning it has a fairly strong correlation level. Conclusion: Based on the study's results, it can be concluded that there was a relationship between BMI and vertebral rotation deformity in adolescents with idiopathic scoliosis.